Application of business process reengineering (BPR) in container stowage planning process - Ong, Kah Hin (2015)
Stowage planning has serious safety, commercial and operational implications for container vessels and is of vital importance to terminal operators and shipping companies. Seaborne container transport offers a cost-efficient and environmentally sustainable mode of freight transport, facilitating global trade. Due to the shipping companies’ drive to reduce cost, good stowage planning should not be ignored and business process reengineering (BPR) could be the tool to drive that improvement. While studies have shown that many organisations across various industries have benefitted from the application of BPR, Yang (2011) mentioned that 75% of BPR projects failed to achieve their desired outcome. Thus, it is crucial that CSF are studied and deployed to enhance the success rate of the BPR initiative. This paper aims to improve the effectiveness and efficiency of the stowage planning process for container vessels through the application of BPR. In this paper, the current stowage planning process will be explored extensively to investigate some of its existing and potential issues. Some of the current issues include the slow response time to loadlist revisions and repetitive work done by the planners from both the terminals and shipping lines. The BPR framework by Sethi & King (1998) was modified to fit the context of this project and used to reengineer the stowage planning process. To conduct this research, empirical observations, preliminary and in-depth interviews, literature reviews and simulations will be conducted. To ensure the feasibility and practicality of the reengineered stowage process, industry practitioners, such as terminal planners, stowage planners and masters, which represent the key parties in the stowage process was targeted for both interviews. In total, 13 industry practitioners was interviewed in this research project. In total, two reengineer processes were crafted (R1 and R2). Through the simulations, R1 and R2 can achieve a cost saving of up to USD$2784 per port call. This cost saving will be increased by USD$4640 if there were any late changes to the stowage plan. Despite the high cost savings, the interviewees doubt that the reengineered processes will be adopted in the short-run except for feeder services. However, most agreed that the reengineered process may be feasible in the lost-run if certain critical success factors (CSF) were met. One of the issue limiting R1’s effectiveness and feasibility will be the lack of coordination and inability to have a good understanding of the trade patterns. Thus, R2 was crafted through BPR to overcome this issue. Among the many CSFs that were identified for both R1 and R2, the issues of culture and availability of relocation opportunities were common for both processes. Through the interviews and simulation, it is recommended that R1 and R2 be adopted for feeder service and multi-port service respectively. Due to the low number of industry practitioners with a terminal background, it was recommended that future research be conducted to gather more feedbacks from the terminal community.